Genome-wide association identifies genomic regions influencing fillet color in Northwest Atlantic salmon (Salmo salar Linnaeus 1758) - Langille, Barbara L.; Sae-Lim, Panya; Boison, Solomon; Wiper, Philip G.; Garber, Amber F. (Frontiers in Genetics, 2024)
Atlantic salmon (Salmo salar) is an important source of food globally; however, fillet color can significantly affect consumer purchasing, leading to potential food waste. Fish diet can be supplemented with astaxanthin to increase the organic pigment, carotenoid, responsible for flesh coloration, however, there is variation in the amount of overall fillet coloration in response to feeding astaxanthin. The uptake of this pigment is influenced by the environment and genetics and has been shown to be heritable. Therefore, we set out to determine the genomic associations of two separate year classes of farmed North American Atlantic salmon with measured Minolta Chroma Meter (lightness, redness, and yellowness) and SalmoFan phenotypic traits. Using ASReml-R genome-wide association, two genetic markers on chromosome 26 were significantly associated with almost all color traits and these two markers explained between 6.0 and 12.5% of the variances. The genomic region on chromosome 26 was importantly found to be associated with the beta-carotene oxygenase 1 (bco1) gene, which is essential in the conversion of beta-carotenoids to vitamin A, implying this gene may also play an important role in flesh coloration in North American Atlantic salmon. Additionally, there were several genomic regions significantly associated with color traits, in which the accompanying genes had functions in line with thermogenesis, immune function, and pathogenic responses. Understanding how environmental and genetic factors work together to affect fillet quality traits will help to inform genetic improvement.